Metallocenic polyolefin composites with siloxane polymer additives - Satti, Angel Jose (2018)
Blends and composites were obtained by mixing commercial metallocenic linear low density polyethylene (LLDPE) and isotactic polypropylene, with different molecular weight polydimethylsiloxanes (PDMS), including a vinyl ended PDMS. Gamma ray irradiation at different atmospheres was also applied in order to enhance blending by grafting and crosslinking of the radioinduced radicals. Dynamic rheological behavior results suggested that blending increased the viscoelasticity of the blends. Improvement and changes in the abrasive wear behavior was also followed, along with structural properties.